PENGASUHAN IBU, KETERLIBATAN AYAH DALAM PENGASUHAN, DAN PERKEMBANGAN KOGNITIF ANAK USIA 2-3 TAHUN DI WILAYAH PREVALENSI STUNTING - Aritonang, Sartika Dewi; Hastuti, Dwi; Puspitawati, Herien (Jurnal Ilmu Keluarga dan Konsumen, 2020)
Mothers and fathers have the same role in parenting, but the role of fathers in parenting is still in the low category especially in Indonesia. The research purpose was to analyze the influence of family characteristics, child characteristics, mothering, and father involvement in parenting on child cognitive development. This study used a cross-sectional study design. The study was conducted in Cibatok Dua Village, Cibungbulang Sub District, Bogor Regency as a representative of the stunting high-prevalence area. Respondents were selected purposively. The population was 154 children from nine Posyandu with a total sample of 100 children aged 2-3 years and their families and selected using a simple random sampling technique. Data analysis used descriptive analysis and multiple linear regression analysis. Descriptive analysis results show that father involvement in parenting and child cognitive development is in a low category and there are no differences between boys and girls. However, mothering is in a low category and there are differences between boys and girls. The results of the regression test found that there was a significant positive effect of child age, family income, and father involvement in parenting on child cognitive development. The results of the research indicate that the child’s age, family income, and father involvement in parenting have a positive significant effect on child cognitive development.